2012
DOI: 10.1016/j.bbamcr.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

De-ubiquitinating proteases USP2a and USP2c cause apoptosis by stabilising RIP1

Abstract: Dynamic ubiquitination impacts on the degradation of proteins by the proteasome as well as on their effects as signalling factors. Of the many cellular responses that are regulated by changes in ubiquitination, apoptosis has garnered special attention. We have found that USP2a and USP2c, two isoforms of the ubiquitin-specific protease USP2, cause cell death upon ectopic expression. We show that both USP2 isoforms can control the ubiquitination status of many proteins but from a panel of potential targets only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Immunofluorescence analysis of HELA cells transfected with the plasmids of USP2-201 or USP2-202 showed that USP2-201 and USP2-202 proteins were both dispersed around nucleus and adjacent to the endoplasmic reticulum while didn't coincide with mitochondria and Golgi. The similar sub-cellular location of USP2-201 and USP2-202 protein was also observed in MCF7 cells transfected with the plasmids of them 26 . Further immunofluorescence localization of GFP-USP2-201 fusion protein in HELA cells proved that GFP-USP2-201 protein localized in early endosomes involved in EGFR degradation cycle 27 .…”
Section: The Alternative Splicing Products Of Usp2 Gene and Their Dissupporting
confidence: 72%
“…Immunofluorescence analysis of HELA cells transfected with the plasmids of USP2-201 or USP2-202 showed that USP2-201 and USP2-202 proteins were both dispersed around nucleus and adjacent to the endoplasmic reticulum while didn't coincide with mitochondria and Golgi. The similar sub-cellular location of USP2-201 and USP2-202 protein was also observed in MCF7 cells transfected with the plasmids of them 26 . Further immunofluorescence localization of GFP-USP2-201 fusion protein in HELA cells proved that GFP-USP2-201 protein localized in early endosomes involved in EGFR degradation cycle 27 .…”
Section: The Alternative Splicing Products Of Usp2 Gene and Their Dissupporting
confidence: 72%
“…This is particularly evident following the recent publication by Mahul-Mellier on Hela and MCF7 breast cancer cells, where downregulation of USP2a by siRNA promotes NF-kB activation and protects cells against TNF-induced cell death, as a consequence of the impairment of the USP2a-TRAF protein ratio. 43, 44 …”
Section: Discussionmentioning
confidence: 99%
“…Frequently the activity of deubiquitinating enzymes is regulated by interactions with various binding partners. TRAF2 can bind to Usp2a which inhibits its effect on K48 but not K63 linked poly-ubiquitin chains, consequently the ratio between TRAF2 and Usp2a determines cells sensitivity to cell death [ 76 ]. Usp10, alongside Usp13, is regulated by binding to Beclin-1 which affects their protein stability, activity and subsequent deubiquitination of target proteins [ 77 ].…”
Section: Regulation Of Epigenetics By Deubiquitinationmentioning
confidence: 99%